2015
DOI: 10.1158/0008-5472.can-14-0036
|View full text |Cite
|
Sign up to set email alerts
|

Cables1 Complex Couples Survival Signaling to the Cell Death Machinery

Abstract: Cables1 is a candidate tumor suppressor that negatively regulates cell growth by inhibiting cyclin-dependent kinases. Cables1 expression is lost frequently in human cancer but little is known about its regulation. Here we report that Cables1 levels are controlled by a phosphorylation and 14-3-3 dependent mechanism. Mutagenic analyses identified two residues, T44 and T150, that are specifically critical for 14-3-3 binding and that serve as substrates for phosphorylation by the cell survival kinase Akt, which by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Our data show that Cables1 competes with PSMA3 to bind p21, and protects p21 from PSMA3mediated proteasomal degradation; the expression level of Cables1 is correlated with that of p21 in human lung cancer tissues (Shi et al, 2015a). Additionally, we found a phosphorylation-dependent and 14-3-3-mediated mechanism that regulates the tumor suppressor function of Cables1 (Shi et al, 2015b). Akt directly interacts with and phosphorylates Cables1 to recruit 14-3-3 to the complex; activated Akt is able to prevent cell apoptosis induced by Cables1 (Shi et al, 2015b).…”
Section: The Role Of Cables1 In Cancermentioning
confidence: 54%
See 3 more Smart Citations
“…Our data show that Cables1 competes with PSMA3 to bind p21, and protects p21 from PSMA3mediated proteasomal degradation; the expression level of Cables1 is correlated with that of p21 in human lung cancer tissues (Shi et al, 2015a). Additionally, we found a phosphorylation-dependent and 14-3-3-mediated mechanism that regulates the tumor suppressor function of Cables1 (Shi et al, 2015b). Akt directly interacts with and phosphorylates Cables1 to recruit 14-3-3 to the complex; activated Akt is able to prevent cell apoptosis induced by Cables1 (Shi et al, 2015b).…”
Section: The Role Of Cables1 In Cancermentioning
confidence: 54%
“…Additionally, we found a phosphorylation-dependent and 14-3-3-mediated mechanism that regulates the tumor suppressor function of Cables1 (Shi et al, 2015b). Akt directly interacts with and phosphorylates Cables1 to recruit 14-3-3 to the complex; activated Akt is able to prevent cell apoptosis induced by Cables1 (Shi et al, 2015b).…”
Section: The Role Of Cables1 In Cancermentioning
confidence: 74%
See 2 more Smart Citations
“…Indeed, later studies demonstrated that loss of CABLES1 enhanced tumor progression in the Apc(Min/+) mouse model, which may be a consequence of increased activation of the Wnt/β-catenin pathway [40]. It was also shown that CABLES1 overexpression induced apoptosis and inhibited cell growth at least in part through p21 stabilization [41,42], further consolidating that CABLES1 acts as a tumor suppressor. Moreover, CABLES1…”
Section: Atypical Cyclins For Novel Functions?mentioning
confidence: 99%